Finite strain elastoplastic constitutive model of saturated soil - Tianci WENG; Yonglin XIONG; Zhe HAN (Shuiwen dizhi gongcheng dizhi)
During the construction of urban underground engineering projects, soils are typically in a saturated state, and many underground engineering accidents are closely related to the large deformation behavior of saturated soils. However, most constitutive models are developed under small strain conditions. To better understand the mechanical characteristics of large deformation in saturated soils, this study applied finite strain theory, combining hyper-elastic and modified Cambridge models. The concept of subloading and superloading yield surfaces was introduced to describe the characteristics of overconsolidation and structure of soils. Utilizing the advantages of numerical computation, a return mapping algorithm was employed to solve the nonlinear response of the constitutive model and derive a consistent tangent stiffness matrix to accelerate convergence and improve computational accuracy. In the principal stress space, a finite strain elastoplastic constitutive model for saturated soils is established, which simultaneously considering structural characteristics, overconsolidation properties, and large deformation mechanical behaviors. Through comparison between experimental data and model calculations, the accuracy of the constitutive model is verified. Additionally, the study investigated the effects of initial overconsolidation ratio, initial structural characteristics, overconsolidation control parameters, and structural control parameters on soil mechanical behavior by simulating isotropic triaxial drained shear tests and triaxial consolidation tests. The results indicate that with increasing overconsolidation ratio, the peak strength of the soil gradually increases, but the final volumetric behavior transitions from shear compaction to shear dilation. As the initial structural characteristics of the soil strengthen, the peak strength significantly increases, and the degree of strain softening also increases accordingly. Increasing the overconsolidation control parameter or reducing the structural control parameter both lead to an increase in the peak strength of the soil.